(untitled) (Wardah, 2015)
“Hidayah” is a very major capital base for a servant in grabbing and worldly happiness and pleasure hereafter . Because guidance is God's instructions given to man to man walking on the straight path . Religious divide God 's guidance into four levels with different stages . The first stage is followed by instinct senses , then reason and the latter is religion . Guidance that is in a person , past, present and future is the right of Allah preoregatif . No one preacher in the world able to give to others , not to mention the Prophet. Therefore , the authority preachers preaching merely an sich . Through preaching, preachers guide audience (mad'u) to reach the guidance of Allah . in Islamic perspective, guidance serves to give birth to a human who is able to achieve the pleasure of Allah, happy and loved and be intelligent beings grateful.